VALENCE FEATURE OF SOCIAL RELATION VERBS IN SIMPLE SENTENCES - Nabiyeva Zarrina; Sobirova Firuza; Baxadirova Muxiba; Maxmudjonova Mexribon; Young Soon Cho (Journal of Higher Education and Academic Advancement, 2024)
This article gives infromation about the feature of valence of social relation verbs in simple statements. In addition, it provides several notions according valence and integrate valence theory with social relations verbs